2010
DOI: 10.1089/vbz.2009.0058
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofEhrlichia chaffeensisandEhrlichia ewingiiin Ticks from Tennessee

Abstract: Human ehrlichiosis is the second most common tick-borne disease reported in Tennessee after Rocky Mountain spotted fever. Two closely related ehrlichiae, Ehrlichia chaffeensis and Ehrlichia ewingii, are both causative agents of human disease and are transmitted by Amblyomma americanum, the lone star tick. Prevalence rates and distribution patterns of these pathogens among ticks in Tennessee are currently unknown. To understand prevalence and exposure risk of Ehrlichia spp., we tested 616 ticks (309 Amblyomma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 31 publications
(28 reference statements)
6
23
0
Order By: Relevance
“…This is the first confirmation of Panola Mountain Ehrlichia in A. americanum from the state of Tennessee. Cohen et al (2010) did not identify any PME-infected ticks in Tennessee, however the 16S rRNA PCR employed in that study is not expected to detect PME (A. Loftis, pers.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This is the first confirmation of Panola Mountain Ehrlichia in A. americanum from the state of Tennessee. Cohen et al (2010) did not identify any PME-infected ticks in Tennessee, however the 16S rRNA PCR employed in that study is not expected to detect PME (A. Loftis, pers.…”
Section: Discussionmentioning
confidence: 79%
“…We documented low-prevalence E. chaffeensis, E. ewingii, and PME infection among A. americanum from both of our study areas. Cohen et al (2010) tested small numbers of A. americanum (mean sample size ∼10/county) from numerous Tennessee counties in 2007-08 and found E. chaffeensis in 2.6% of 309 ticks and E. ewingii in 0.8% of 238 ticks. Combining E. chaffeensis and E. ewingii, prevalence did not differ significantly between their study (3.2%) and ours (4.0%; P = 0.57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human monocytotrophic ehrlichiosis is most commonly reported from the southeastern and south central United States. 34 The A. americanum tick is also a vector for Ehrlichia ewingii , 35,36 the cause of granulocytic ehrlichiosis in humans. [37][38][39] Thirteen cases of ehrlichiosis were reported in Kentucky in 2008, a 325% increase over 2007.…”
Section: Introductionmentioning
confidence: 99%
“…13 In Tennessee, 2.6% of A. americanum ticks were found to be infected with E. chaffeensis , and 0.8% were infected with E. ewingii , and no other Amblyommma , Ixodes , or Dermacentor ticks tested were positive for any Ehrlichia spp. 36 In a study conducted during 1996-2001, whitetailed deer from eight states were tested for E. ewingii by PCR. It was found that 5.5% were positive for E. ewingii infection, including one deer from Kentucky.…”
mentioning
confidence: 99%